The role of credited co-curricular programmes on the internationalization and infusing values into student’s personality: the IIUM model - Shuriye, Abdi Omar (Scholarlink Resource Centre Ltd., 2011)
Credited co-curricular programmes are skills and proficiencies aimed at helping students to achieve extra competences within the academic syllabus or the main programme of study. The aim is to produce qualified and disciplined graduates with leadership and teamwork qualities. This paper evaluates the International Islamic University of Malaysia’s experience in establishing, maintaining and promoting its unique model of credited cocurricular programmes.